A generalized model of lead rubber bearing considering large strain stiffening and degradation. (15th January 2023) - Chen, Peng; Wang, Bin; Zhang, Zhanhong; Li, Tao; Dai, Kaoshan
Highlights: A generalized Bouc–Wen model is proposed to accurately model lead rubber bearings. The generalized model is concise and can represent large strain mechanical properties. Dynamic response comparison proves the improvement of the modeling accuracy. Abstract: Lead rubber bearings (LRBs) have been widely used in seismic isolation systems to mitigate earthquake damage in regions characterized by high seismic intensity. However, effective isolation is achieved at the expense of largely concentrated displacement in the isolation layer. Past experimental studies have confirmed that rubber stiffening and degradation properties are essential for LRBs at large cyclic strains. That is, accurately simulating the complex nonlinear behavior of LRBs is significant to evaluate the performance of isolated structures under strong earthquakes. Nevertheless, most LRB models in engineering practice cannot capture the strong nonlinear properties and the existing models for elaborate modeling are not widely used due to the complicated shape parameters. For this reason, the present study proposes a generalized Bouc–Wen model that can reasonably reflect the large strain stiffening and strength degradation properties of rubber. The traditional Bouc–Wen model of LRBs was introduced first. Subsequently, a generalized Bouc–Wen model of LRBs that is capable of simulating the observed large cyclic behavior with reasonable accuracy was developed. The model was further verified by the experimental results of LRBs with different design parameters under various loading conditions. Moreover, time history analyses were conducted to evaluate the earthquake responses of the single-degree-of-freedom system with the traditional Bouc–Wen and generalized Bouc–Wen model. Comparison proves that the two bearing models can closely estimate the peak deformation and shear force in minor and moderate earthquakes. By contrast, the generalized model can accurately capture the LRB properties under large cyclic strain that can restrain the bearing deformation but possibly increase the shear force significantly under strong earthquakes.